Examining Leadership Characteristics at International Multilaterals - Agota Giedre Raisiene; Aleksandra Pulokiene; Andrius Valickas (Montenegrin Journal of Economics)
The paper discusses leadership characteristics in international projects that require cooperation. The influence of the leader's traits and qualities on the implementation of the multilateral project was studied under the framework of the Latvia-Lithuania-Belarus TransBorder Cooperation Program. A multistage survey in different target groups was used for the research. The research revealed that there is no discrepancy between the effective leadership at multilaterals and effective leadership concepts in general. Nevertheless, some specific leader’s characteristics and qualities can be underlined. Multilateral projects require leader to be competitive, self-confident, visionary and supportive at first. Herewith, the leader must have good knowledge on the project technical requirements, an ability to consult project team on performance, a capability to coordinate and to control project processes, a capacity to effectively manage project documentation, a competence of mentoring and employee engagement, an ability to meet project team needs, and perfect skills of project internal and external communication. The research also revealed that cultural differences of team members can determine the attitude towards leadership.